Oportunidades y peligros del pluralismo sindical en el Chile post-transición - Francisca Gutiérrez Crocco (Nuevo mundo - Mundos Nuevos, 2013)
The coup of 1973, begins a crisis on Chilean trade unionism: unionization rates decreases dramatically. However, the situation changes in the late 1990's and the unions regain a part of the lost quota. Unlike other tests that put the emphasis on purely political or economic factors, we argue that this is largely due to domestic factors. The increased visibility of the Central Unitaria de Trabajadores (CUT) alternative union models, has made unionism attractive for workers before distant. We try to demonstrate this hypothesis in two steps: 1. From the analysis of statistical data, we report the fragmentation of trade unions; 2. From the analysis of thirty interviews, we identified three models of unionism and the relationship between them. Finally, we try to expose some of the dangers of this trade union pluralism, to demonstrate that the regain of unionization, as it has been until now, has also serious costs for Chilean trade unionism.